2021
DOI: 10.3389/fevo.2021.556821
|View full text |Cite
|
Sign up to set email alerts
|

Community and Species-Level Changes of Insect Species Visiting Mangifera indica Flowers Following Hurricane María: “The Devil Is in the Details”

Abstract: Mangifera indica is a widespread economically important tropical fruit. An ongoing study at the Juana Diaz Experimental Station in Puerto Rico aims to understand the factors that influence local pollination success and fruit yields in four fields each hosting a different mango cultivar (Keitt, Kent, Tommy Atkins, and Julie) at different temporal scales. Here we describe the results of insect collection campaigns that evaluated flower visitor communities of these fields (from January to April) in the seasons of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 75 publications
(104 reference statements)
0
4
0
Order By: Relevance
“…Effect assessments of the 2017 Atlantic hurricane season demonstrate its broad impact on ecosystems and their trophic levels; for example, beach, mangrove, and forest ecosystems (Barreto‐Orta et al, 2019; Hall et al, 2020; Liu et al, 2018; Walcker et al, 2019), salt and freshwater fish communities (Meléndez‐Vazquez et al, 2019; Neal et al, 2020), insect species and communities (Cabrera‐Asencio & Meléndez‐Ackerman, 2021), birds (Lloyd et al, 2019; Palmer et al, 2018), and sea slugs (Middlebrooks et al, 2020). For St. Eustatius specifically, our data add to the understanding of an ecosystem‐wide hurricane impact during 2017 which, besides iguanas, affected forests (Eppinga & Pucko, 2018), as well as populations of Bridled Quail‐dove (River‐Milan et al, 2021) and Red‐bellied racer (Madden et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Effect assessments of the 2017 Atlantic hurricane season demonstrate its broad impact on ecosystems and their trophic levels; for example, beach, mangrove, and forest ecosystems (Barreto‐Orta et al, 2019; Hall et al, 2020; Liu et al, 2018; Walcker et al, 2019), salt and freshwater fish communities (Meléndez‐Vazquez et al, 2019; Neal et al, 2020), insect species and communities (Cabrera‐Asencio & Meléndez‐Ackerman, 2021), birds (Lloyd et al, 2019; Palmer et al, 2018), and sea slugs (Middlebrooks et al, 2020). For St. Eustatius specifically, our data add to the understanding of an ecosystem‐wide hurricane impact during 2017 which, besides iguanas, affected forests (Eppinga & Pucko, 2018), as well as populations of Bridled Quail‐dove (River‐Milan et al, 2021) and Red‐bellied racer (Madden et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Effect assessments of the 2017 Atlantic hurricane season are demonstrating its broad impact on ecosystems and their trophic levels; e.g., beach, mangrove and forest ecosystems (Liu et al 2018; Barreto-Orta et al 2019; Walker et al 2019; Hall et al 2020), salt- and freshwater fish communities (Meléndez-Vazquez et al 2019; Neal et al 2020), insect species and communities (Cabrera-Asencio and Meléndez-Ackerman 2021), birds (Palmer et al 2018; Lloyd et al 2019), and seas slugs (Middlebrooks et al 2020). For St. Eustatius specifically, our data adds to the understanding of an ecosystem-wide hurricane impact during 2017 which, besides iguanas, affected both forests (Eppinga and Pucko 2018) and the populations of Bridled Quail-dove (Rivera-Milán et al 2021) and Red-bellied racer (Madden et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, despite overall pollinator decline and plant defoliation immediately following hurricanes, plant–pollinator relationships involving Lepidoptera display adaptability and resilience (Ackerman & Moya, 1996; Cabrera‐Asencio & Meléndez‐Ackerman, 2021). More work is needed to understand the long‐term effects of hurricane damage on Lepidoptera populations.…”
Section: Ecologymentioning
confidence: 99%
“…Pollination of tropical crops is predominately facilitated by insect visitors in the order Hymenoptera, though adult butterflies and moths also play a documented role (Roubik, 1995). For example, a recent study in Puerto Rico found that Lepidopterans were among 50 mango crop pollinator species ( Mangifera indica ; Cabrera‐Asencio & Meléndez‐Ackerman, 2021). While it is challenging to elucidate general patterns regarding pollination efficiency across tropical crops, a worldwide literature search concluded that the families Nymphalidae and Pieridae may be the most significant crop pollinators within Lepidoptera (Rader et al., 2020).…”
Section: Agriculturementioning
confidence: 99%